Book review: Ziemie Obiecane. Rolnictwo Dolnego Śląska w Latach 1945–1956 w ujęciu ekonomicznym i historycznym [Promised Lands: Agriculture of Lower Silesia in the Years 1945–1956 from the Economic and Historical Point of View] - Błażejczyk-Majka, Lucyna (Studia Historiae Oeconomicae, 2024)
The review of the book titled Ziemie obiecane. Rolnictwo Dolnego Śląska w latach 1945–1956 w ujęciu ekonomicznym i historycznym [Promised Lands: Agriculture of Lower Silesia in the years 1945–1956 from the economic and historical point of view] that was written by Sylwia Straszak–Chandoha and published in 2021 by the Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu [Publishing House of the Wroclaw University of Economics and Business]. The book describes the problem of settlement, which is rarely discussed in the literature on the subject, and, in particular, the organization of agricultural production in Lower Silesia in the first few years after the end of World War II.